2017
DOI: 10.1002/1873-3468.12561
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional communication between sensory neurons and osteoblasts in an in vitro coculture system

Abstract: Recent studies have revealed that the sensory nervous system is involved in bone metabolism. However, the mechanism of communication between neurons and osteoblasts is yet to be elucidated. In this study, we investigated the signaling pathways between sensory neurons of the dorsal root ganglion (DRG) and the osteoblast-like MC3T3-E1 cells using an in vitro coculture system. Our findings indicate that signal transduction from DRG-derived neurons to MC3T3-E1 cells is suppressed by antagonists of the AMPA recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…In several studies, the coculture system had been used to investigate the communication between neurons and other cells [ 16 , 40 43 ]. It was reported that DRG could promote the proliferation of osteoblasts differentiated from BMSCs and the osteogenic gene expression under direct contact condition [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the coculture system had been used to investigate the communication between neurons and other cells [ 16 , 40 43 ]. It was reported that DRG could promote the proliferation of osteoblasts differentiated from BMSCs and the osteogenic gene expression under direct contact condition [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the ongoing debate on which joint tissues give rise to pain in OA (nociceptive versus neuropathic) 35 , the bioelectric concept has some merit since sympathetic and sensory fibres densely innervate bone and joint tissues like the synovium, and can modulate inflammation, vascularization, matrix differentiation, and bone mass 34 . Kodama and colleagues have also recently proposed that osteoblasts, and possibly other bone surface cells, might serve as 'sensors' for environmental stimuli and transmit this perception to the CNS via afferent nerves 36 . Sensory nerves have even been observed in contact with a subpopulation of chondrocytes at the surface of articular cartilage 37 .…”
Section: P 89mentioning
confidence: 99%
“…In a very recent study, Kodama et al describe a bi-directional communication of osteoblastic MC3T3-E1 cells and dorsal root ganglion-derived sensory neurons [91]. The authors show that the efferent signal is transmitted via SP and glutamate and that osteoblast-like cells communicate to the afferent neural arm via adenosine triphosphate (ATP) exocytosis after perception of an inflammatory stimulus like bradykinin.…”
Section: Sensory and Sympathetic Neurotransmitters And Their Recepmentioning
confidence: 99%